Batch process heat storage integration: A simple and effective graphical approach. (15th October 2019) - Abdelouadoud, Yasmina; Lucas, Edward; Krummenacher, Pierre; Olsen, Donald; Wellig, Beat
Abstract: The improvement of thermal energy use in batch and semi-continuous processes utilizing established techniques such as Pinch Analysis faces challenges as direct heat recovery is restricted and schedule dependent, limiting broad industrial application. In overcoming this limitation, sensible heat storage integration has proven to be effective in achieving significant and less schedule-sensitive heat recovery but designing solutions is problematic given the complex trade-offs that occur. The presented graphical design method relies on the Indirect Sources Sinks Profiles (ISSPs) which extends the scope of time-average models and brings a systematic foundation to the design procedure. Graphical assignment zones are introduced to represent on the ISSPs constraints and degrees of freedom that apply when designing the Heat Exchanger and Storage Network (HESN) that can achieve the target heat recovery, given by ISSP overlap. A general procedure for their determination is presented, alongside resulting HESN designs for a case study process which achieve utility reductions of 35.0% up to 76.0%. Designs are automatically balanced making them functional concepts without manual adjustment, and although not cost-optimized, are inherently reduced in complexity by the method and suitable for further stepwise improvement. Graphical abstract: Image 1056 Highlights: A novel graphical method for batch process heat storage integration is presented. Algorithmically determined "assignment zones" facilitate storage design decisions. Functional conceptual designs are created, achieving up to 76.0% utility reduction. Utility reduction is comparable to that found by mathematical approach. Alternate designs are rapidly generated and offer insights to system constraints.